Cultural factors influencing COVID-19-related perceptions and behavior, seen from immigrants' own perspective - a qualitative study in Norway - Solveig Vederhus; Eirik Myhre; Esperanza Diaz; Liv Grimstvedt Kvalvik (BMC, 2024)
Abstract Background Cultural factors are often mentioned as a possible explanation for the observed differences between immigrant populations compared to general populations with regards to COVID-19 disease burden and vaccination rates, but usually without any further exploration of what this entails. This paper aims to capture the thoughts of immigrants themselves and explore how they think culture may or may not have affected vaccination rates and health behavior during the pandemic. Methods We performed qualitative interviews with 18 immigrants from Poland, Somalia and Sri Lanka living in Norway. Group interviews and individual interviews were transcribed and analyzed using systematic text condensation. Results We identified four main themes the participants thought could influence spread of infection and vaccine hesitancy: cultural factors, transcultural factors, host society factors, and other personal factors. Social habits, religious traditions, attitudes towards and trust in the healthcare system, sense of community and societal duty were understood as cultural factors that influenced health behavior and vaccination hesitancy. However, different cultural factors could have varied impact on immigrants' behavior related to COVID-19 and possibly other health settings for different immigrant groups. In addition, we found examples of other factors related to being 'between cultures', and we found structural and socioeconomic factors not linked to culture. Conclusions Our paper brings awareness to how rules and guidelines may hit harder and interfere more in the way of life in some communities than others. In the continued work towards equity in health promotion and healthcare services, policymakers ought to keep the existence of such cultural differences in mind, to be able to make policies well fitted to ensure good health and quality of life for all.